The Practical Application of the Individual Care Plan for Pediatric Palliative Care: A Mixed-Method Study - Chantal Y. Joren; Judith L. Aris-Meijer; Leontien C. M. Kremer; Suzanne C. Hofman; Hester Rippen-Wagner; Ria Slingerland-Blom; Chantal van der Velden; Meggi A. Schuiling-Otten; Project Team ICP; A. A. Eduard Verhagen; Marijke C. Kars (MDPI AG, 2024)
Background/Objective: The Individual Care Plan (ICP) for pediatric palliative care was developed to provide person-centered care for the individual child and family. Currently, a lack of clarity remains regarding the use and function of the ICP in daily practice. To further implement the ICP, it is important to identify how parents and healthcare professionals use the ICP and which obstacles or benefits are experienced. Methods: This mixed-method study used qualitative interviews and quantitative questionnaires in (bereaved) parents and healthcare professionals with experience with the ICP. Results: Parents and healthcare professionals used the ICP to establish a joint plan for care and treatment of the child to coordinate care and to achieve child- and family-centered care. This includes both obstacles that complicate achieving care goals and benefits that make it easier. Furthermore, responsibilities for the ICP remained unclear, and there was no set point in the illness trajectory for drawing up the ICP. Conclusions: Parents and healthcare professionals use the ICP as intended. However, uncertainties regarding timing, roles and responsibilities prevent optimal use of the ICP. Agreements on timing and responsibilities are needed for further ICP implementation in daily pediatric palliative care practice.